The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1039/b811842f
|View full text |Cite
|
Sign up to set email alerts
|

In situ techniques in biomimetic mineralization studies of calcium carbonate

Abstract: The often astonishing material properties of crystalline biominerals are generally related to the hierarchical assembly of specifically interacting organic and inorganic components. To synthesize new materials with similar advanced properties applying nature's biomimeralization strategies we need to unravel the mechanisms of biologically and biomimetically controlled mineral formation. Since the literature is extensive this tutorial review is focussed on CaCO(3), the most abundant biomineral. We will first rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 66 publications
1
85
0
7
Order By: Relevance
“…In many cases, the precipitation of CaCO 3 from solution is described as a multistep process, with amorphous phases first precipitated before transformation to more stable crystalline forms according to Ostwald's rule of stages (9). Moreover, in biological systems, time-dependent spectroscopy measurements indicated that a hydrated amorphous calcium carbonate (ACC) is first deposited and then undergoes dehydration before crystallization (10).…”
mentioning
confidence: 99%
“…In many cases, the precipitation of CaCO 3 from solution is described as a multistep process, with amorphous phases first precipitated before transformation to more stable crystalline forms according to Ostwald's rule of stages (9). Moreover, in biological systems, time-dependent spectroscopy measurements indicated that a hydrated amorphous calcium carbonate (ACC) is first deposited and then undergoes dehydration before crystallization (10).…”
mentioning
confidence: 99%
“…Although acidic macromolecules are known to affect growth habits and phase selection, or even to completely inhibit precipitation in solution (Sommerdijk & With, 2008;Meldrum & C€ olfen, 2008;Gower, 2008), little is known about the role of matrix-immobilized acidic macromolecules in directing mineralization. This lack of understanding is, in part, due to the difficulty of studying biomimetic mineralization systems with sufficient spatial and temporal resolution (Dey et al, 2010). However, liquid phase transmission electron microscopy (LP-TEM) can visualize events in situ in thin liquid volumes (about 500 nm in height) confined within two electron transparent silicon nitride (SiN) membranes.…”
Section: In Situ Observations Of Biomineralization Processesmentioning
confidence: 99%
“…Damit können Ansätze, die aus dem biologischen Gebiet stammen, wirkungsvoll mit solchen aus den Materialwissenschaften kombiniert werden. [50] Wir danken P. H. H. Bomans für seine Unterstützung bei der Durchführung der Kryo-TEM. Die beschriebenen Forschungsarbeiten werden vom Dutch Polymer Institute (DPI) (Fördernummer 688) unterstützt.…”
Section: Schlussfolgerungen Und Ausblickunclassified